2003
DOI: 10.1021/ol0348147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Novel Radical Trapping and Carbonyl Group Trapping Anti-AGE Agent:  A Pyridoxamine Analogue for Inhibiting Advanced Glycation (AGE) and Lipoxidation (ALE) End Products

Abstract: [structure: see text] Pyridoxamine is known to be an effective inhibitor of both advanced glycation (AGE) and advanced lipoxidation (ALE) end products. The synthesis of a novel multifunctional AGE and ALE inhibitor, 6-dimethylaminopyridoxamine (dmaPM, 11) is described. The 6-dimethylamino substituent increases the radical trapping ability of pyridoxamine's phenolic group. Results obtained during ribose glycations show that both the new dmaPM and a known strong radical trapping agent, 6-hydroxy-2,5,7,8-tetramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…On the basis of their structures, many of the AGE inhibitors tested are probably multifunctional but, nevertheless, they can still be classified as follows: 1) radical traps: 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox or Tx), dmaPM, and dmaPN (these three compounds have been shown to have comparable abilities to retard allophycocyanin fluorescence quenching induced by peroxyl radicals (59), and allophycocyanin fluorescence quenching was retarded by o-PD at a level intermediate between PN and Tx); 2) carbonyl traps: dmaPM, PM, AG, and o-phenylenediamine (o-PD); and 3) chelators: dmaPM, PM, and diPM (other potential weaker chelators are AG, o-PD, dmaPN and PN). The three compounds classified as radical-trapping antioxidants, Tx, dmaPM, and dmaPN, gave an astonishing increase in the yields of pentosidine in both ϩM buffer (3-6-fold) and ϪM buffer (4.5-7-fold), as shown in Fig.…”
Section: Unexpected Increase In Pentosidine Yields During Ribosementioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of their structures, many of the AGE inhibitors tested are probably multifunctional but, nevertheless, they can still be classified as follows: 1) radical traps: 6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid (Trolox or Tx), dmaPM, and dmaPN (these three compounds have been shown to have comparable abilities to retard allophycocyanin fluorescence quenching induced by peroxyl radicals (59), and allophycocyanin fluorescence quenching was retarded by o-PD at a level intermediate between PN and Tx); 2) carbonyl traps: dmaPM, PM, AG, and o-phenylenediamine (o-PD); and 3) chelators: dmaPM, PM, and diPM (other potential weaker chelators are AG, o-PD, dmaPN and PN). The three compounds classified as radical-trapping antioxidants, Tx, dmaPM, and dmaPN, gave an astonishing increase in the yields of pentosidine in both ϩM buffer (3-6-fold) and ϪM buffer (4.5-7-fold), as shown in Fig.…”
Section: Unexpected Increase In Pentosidine Yields During Ribosementioning
confidence: 99%
“…Pratt et al (36) have shown that strong electron-donating groups (such as dimethylamino) para to the phenolic hydroxyl group of 3-pyridinols and 5-pyrimidinols decrease the O-H bond dissociation enthalpy and greatly increase radical trapping rates but do not lower the ionization potential to the point that there is a direct reaction with oxygen. Therefore, PM was modified by the addition of a 6-dimethylamino substituent (6-dimethylaminopyridoxamine, dmaPM) (59). A pyridoxine (PN) derivative (6-dimethylaminopyridoxine, dmaPN) was also tested to study the importance of the nucleophilic amine group during glycation reactions.…”
mentioning
confidence: 99%
“…Pyridoxamine is one of the three natural forms of vitamin B6. To date, many independent in vitro and in vivo studies have shown that pyridoxamine strongly inhibits the production of AGEs (12,13). Reactive carbonyl compounds are the precursors of AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that pyridoxamine strongly inhibits the production of AGEs both in vitro and in vivo (12,13). Pyridoxamine is also a free radical scavenger.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs like metformin [112][113][114] and buformin [115] also showed the potential to protect proteins against in vitro glycation and cross-linking [116,117]. Furthermore, a series of compounds, such as calcium antagonists [118], amlodipine [119], kinetin [120], quinine [121], and synthetic 6-dimethylaminopyridoxamine [122], retarded or suppressed AGE formation possibly due to radical scavenging properties. In one study, the inhibitory activity of isoferulic acid (IFA) on fructose-and glucose-mediated protein glycation and the oxidation of bovine serum albumin (BSA) was investigated [123].…”
Section: Therapy For Age-mediated Neurodegenerative Diseases With Synmentioning
confidence: 99%